The secret box - Ringwald, Whitaker (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2013)
"On her twelfth birthday, Jax Malone receives an odd, unopenable present from an estranged aunt. When Jax and her cousins Ethan and Tyler go on a quest to open the box, they uncover a mystery with magical consequences"--